DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING ARTICULATE STORYLINE 3 ON THE PLANE FIGURE MATERIALS - Novita Anggraini; Resyi A. Gani; Nurlinda Safitri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The development of interactive learning media using Articulate Storyline 3 on plane figure material aims to determine the development and feasibility of product development through interactive learning media. The research methodology used is Research and Development with the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation) with the research subject of students at class IV-C SDN Julang Bogor. The instruments used in the research are media expert validation sheets, linguists and material experts with a total of three experts, students and teacher response instruments, and pre-test and post-test instruments. The validation results produce an average score of 93.7% with the "Very Feasible" criteria. Moreover, the results of the pre-test and post-test assessment produce an N-Gain score of 0.70 with the "High" criteria. Students’ responses indicate 98.7% and teachers’ responses indicate 88% with the "Very Good" criteria. Based on the results, the development of interactive learning media using Articulate Storyline 3 on plane figure material in class IV SDN Julang Bogor meets the criteria of validity and feasibility for its development, especially on plane figure material.